The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/land10030309
|View full text |Cite
|
Sign up to set email alerts
|

Soil Carbon Regulating Ecosystem Services in the State of South Carolina, USA

Abstract: Sustainable management of soil carbon (C) at the state level requires valuation of soil C regulating ecosystem services (ES) and disservices (ED). The objective of this study was to assess the value of regulating ES from soil organic carbon (SOC), soil inorganic carbon (SIC), and total soil carbon (TSC) stocks, based on the concept of the avoided social cost of carbon dioxide (CO2) emissions for the state of South Carolina (SC) in the United States of America (U.S.A.) by soil order, soil depth (0–200 cm), regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Several counties had development in agriculturally productive soils (Alfisols and Mollisols) which are commonly considered to be soil carbon hotspots with higher SC-CO 2 . In South Carolina, these agriculturally productive soils are relatively rare and represent less than 10% of the total state area, compared to Ultisols, which cover 70% of South Carolina [15]. Over time, loss of productive agricultural soils to development can reduce local food security.…”
Section: Land Cover Change In South Carolinamentioning
confidence: 99%
See 2 more Smart Citations
“…Several counties had development in agriculturally productive soils (Alfisols and Mollisols) which are commonly considered to be soil carbon hotspots with higher SC-CO 2 . In South Carolina, these agriculturally productive soils are relatively rare and represent less than 10% of the total state area, compared to Ultisols, which cover 70% of South Carolina [15]. Over time, loss of productive agricultural soils to development can reduce local food security.…”
Section: Land Cover Change In South Carolinamentioning
confidence: 99%
“…The Southeastern United States and South Carolina are experiencing some of the highest urbanization rates and losses of ecosystem services [12,22]. Mikhailova et al (2020) [15] examined soil C regulating ES in the state of South Carolina and reported the value of the social cost of carbon dioxide (SC-CO 2 ) emissions by soil C type (SOC, SIC, TSC), soil order, region, and county in the context of "avoided" versus potential "realized" social costs of carbon. Although informative, that study lacked integration with LULC change analysis to indicate "hotspots" of potential "realized" social costs of C because of disturbance (change in LULC), especially in the "developed" LULC category.…”
Section: Land Cover Change In South Carolinamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to acting as a substrate for vegetation, soils play a key role in multiple processes, including biogeochemical cycling, biodiversity habitat provision, and extreme event mitigation [1][2][3]. They also contribute significantly to the global carbon cycle [1,[4][5][6][7][8] and store approximately 2500 Gt of carbon [9]. However, current alterations in the ecological functions of soils (biological, hydric, climatic, and agronomic), resulting from their occupation or use, also known as artificialization, strongly affect their capacity to provide ecosystem services [10].…”
Section: Introductionmentioning
confidence: 99%
“…), and is a life cycle in a dynamic equilibrium state [15,16]. Soil offers support to significant global ecosystem services, such as water purification, carbon sequestration, nutrient cycling, and providing habitat for biodiversity [17,18]. Soils contribute to general ecosystem services, defined as "services to society that ecosystems provide," which require collaboration among different disciplines [19].…”
Section: Introductionmentioning
confidence: 99%